MANNAN AND HANNAN TECHNIQUE FOR PRODUCTION OF RABBIT EAR KELOID MODEL - A. M. Babar; A. H. Nagi (Journal of Animal and Plant Sciences, 2017)
Keloids & hypertrophic scars are a type of benign fibrous lesions formed during skin wound repair. Keloids occur exclusively in Homo sapiens, to the exclusion of animals. No operable keloid animal model has been built so far.The authors have developed a novel technique for rabbit ear keloid model creation using Transforming Growth Factor Beta 1 injection, a pro-fibrotic cytokine, followed by composite punch excision.Objective of this study was to produce the best rabbit ear keloid model. Main outcome measure was the best rabbit ear keloid model. It was a quasi-experimental trial, carried out at Experimental Research/Pathology Laboratories, University of Health Sciences, Lahore, Pakistan. Its duration was twelve months, from April 2011 to March 2012.Sample consisted of one New Zealand White rabbit. Technique consisted ofgiving injection of Transforming Growth Factor Beta 1, and subsequently performing ventral skin, ventral perichondrium, cartilage, and dorsal perichondrium excision, leaving behind only dorsal skin.The best rabbit ear keloid model was produced by this technique, which was intact even after follow up of one year.This technique has been named as ‘Mannan&Hannan Technique for production of rabbit ear keloid model’. This technique has not been used before. National and International patents are being applied for.
Keywords: Cicatrix; Hypertrophic; Keloid; Models; Animal; Rabbit; Transforming Growth Factor Beta 1